2021
DOI: 10.18608/jla.2021.7357
|View full text |Cite
|
Sign up to set email alerts
|

ADA for IBL: Lessons Learned in Aligning Learning Design and Analytics for Inquiry-Based Learning Orchestration

Abstract: Orchestrating technology-enhanced learning is a difficult task, especially in demanding pedagogical approaches like inquiry-based learning (IBL). To foster effective teacher adoption, both the complexity of designing IBL activities and the uncertainty about the student learning path during enactment need to be addressed. Previous research suggests that aligning learning design and learning analytics can be an effective way to provide such orchestration support. This paper reports on a design-based research (DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…A similar point has been raised by Krumm et al (2021), who noted the critical importance of understanding the context in which the data is collected and the importance of non-technical activities to support collaboration and educational data sharing. This is also seen by the adoption of design-based research (DBR) by both Rodríguez-Triana et al (2021) and Krumm et al (2021) in their studies. Several studies also highlighted the implications for the professional development of teachers (van Leeuwen et al, 2021) and LA practitioners (Yacobson et al, 2021), as well as the importance of policy (Yacobson et al, 2021) for driving ethical LA adoption.…”
Section: Key Takeaways From This Special Sectionmentioning
confidence: 95%
See 4 more Smart Citations
“…A similar point has been raised by Krumm et al (2021), who noted the critical importance of understanding the context in which the data is collected and the importance of non-technical activities to support collaboration and educational data sharing. This is also seen by the adoption of design-based research (DBR) by both Rodríguez-Triana et al (2021) and Krumm et al (2021) in their studies. Several studies also highlighted the implications for the professional development of teachers (van Leeuwen et al, 2021) and LA practitioners (Yacobson et al, 2021), as well as the importance of policy (Yacobson et al, 2021) for driving ethical LA adoption.…”
Section: Key Takeaways From This Special Sectionmentioning
confidence: 95%
“…The importance of aligning learning analytics and learning design has been explored by the second paper by Rodríguez-Triana et al (2021), who evaluate alignment of (learning) analytics and design (ADA) within the context of inquiry-based learning (IBL). Looking at how instructors use a whole range of orchestration tools, Rodríguez-Triana et al ( 2021) identified a set of design needs to effectively support the orchestration of IBL.…”
Section: Summary Of Special Sectionmentioning
confidence: 99%
See 3 more Smart Citations